Choroid Plexus Cysts: Single Nucleotide Polymorphism Array Analysis of Associated Genetic Anomalies and Resulting Obstetrical Outcomes - Cai M; Huang H; Su L; Wu X; Xie X; Xu L; Lin N (Dove Medical Press, 2021)
Meiying Cai,* Hailong Huang,* Linjuan Su, Xiaoqing Wu, Xiaorui Xie, Liangpu Xu, Na Lin Medical Genetic Diagnosis and Therapy Center, Fujian Maternity and Child Health Hospital, Affiliated Hospital of Fujian Medical University, Fujian Key Laboratory for Prenatal Diagnosis and Birth Defect, Fuzhou, People’s Republic of China*These authors contributed equally to this workCorrespondence: Liangpu Xu; Na Lin Tel +86-0591-87554929Email xiliangpu@fjmu.edu.cn; linna1088@fjmu.edu.cnObjective: Choroid plexus cysts (CPC) are pseudocysts in the fetal choroid plexus and can be detected during ultrasound examination. However, the etiology of fetuses with CPC is still unknown. This study aimed to evaluate the genetic anomalies of fetuses with CPC using single nucleotide polymorphism (SNP) array analysis, as well as their obstetrical outcomes.Patients and Methods: Among 201 fetuses, 108, 69, and 24 had isolated CPC (iCPC), CPC with sonographic soft markers, and CPC with sonographic structural malformations, respectively. All fetuses underwent conventional karyotyping analysis and SNP array analysis.Results: Among 201 fetuses with CPC, 15 had chromosomal abnormalities (7.5%, 15/201), including nine fetuses with trisomy 18. Further, SNP array results were consistent with the conventional karyotype analysis and additionally revealed 6.0% (12/201) abnormal copy number variations (CNVs). The rates of pathogenic CNVs in fetuses with iCPC, CPC combined with sonographic soft markers, and CPC combined with sonographic structural malformations were 6.5%, 6.0%, and 45.8%, respectively, with significant differences among the groups.Conclusion: The results of the SNP array affected the obstetrical outcomes. CPC is thus associated with pathogenic CNVs in approximately 10.9% of cases. Therefore, SNP array should be offered for prenatal testing of fetuses with CPC.Keywords: choroid plexus cysts, SNP, cytogenetic abnormalities, sonographic anomalies